Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/19401736.2015.1060476
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of mitochondrial DNA haplogroups and variants for in vitro fertilization failure in a Han Chinese population

Abstract: In this study, we aimed to investigate the associations of mitochondrial DNA (mtDNA) haplogroups and variants with in vitro fertilization (IVF) failure. A retrospective, comparative study of 260 fresh IVF cycles in a Han Chinese population was performed from July 2011 to April 2014. Seventy-three couples had low fertilization rates (≤30%) or total fertilization failure, and 187 controls with normal fertilization were included. Human sperm mtDNA haplogroups and variants were determined by polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Those studies could support the application of mtDNA haplogroups of the infertile men in forensic caseworks. Mao et al (2016) revealed that males with haplogroup Z might accumulate a higher risk of in vitro fertilization failure in Han Chinese men group. Similarly, the present study revealed that the OAT of Saudi men could be found in H5a, M25 and U7 ATP6 haplogroups.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies could support the application of mtDNA haplogroups of the infertile men in forensic caseworks. Mao et al (2016) revealed that males with haplogroup Z might accumulate a higher risk of in vitro fertilization failure in Han Chinese men group. Similarly, the present study revealed that the OAT of Saudi men could be found in H5a, M25 and U7 ATP6 haplogroups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MT-ND4 might be associated with Chinese male infertility (Ni et al 2017). Our previous study suggested that MT-ATP6 variants might be possible causes of IVF failure, but MT-ND3 homoplasmic variant 10397 might help decrease the risk of IVF failure (Mao et al 2015(Mao et al , 2016. In this study, we discuss the relationship between mitochondrial genes and fertilization failure, laying a foundation for studying the association between fertilization failure and the sperm MT-ND gene variants.…”
Section: Introductionmentioning
confidence: 85%
“…However, another study showed that the mtDNA haplogroup R was a strong, independent predictor of sperm motility in the Han Chinese population, conferring a 2.97-fold decreased chance of asthenozoospermia compared with those without haplogroup R (Feng et al 2013). In addition, our previous study indicated that men with haplogroup Z might inherit a higher risk of IVF failure in the Han Chinese population (Mao et al 2016). Haplogroups D and G are subgroups of haplogroup M, with diagnostic single-nucleotide polymorphism markers m.5178C>A and m.4833A>G, respectively.…”
Section: Association Between Tff and The Haplogroups D And Gmentioning
confidence: 92%
See 2 more Smart Citations